2016
DOI: 10.1371/journal.pone.0162371
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Transport Management Practices Associated with Injuries and Health Problems in Horses

Abstract: An online survey was conducted to determine associations between transport management and transport-related injuries and diseases in horses in Australia. The survey was composed of three sections: respondents’ demographic information, transport management strategies or procedures (before, during and after transportation) and transport diseases experienced in the previous two year period. Univariate and multivariate modelling was performed exploring associations between variables (respondents’ details and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 45 publications
3
42
2
Order By: Relevance
“…Abdominal auscultation also suggested decreased GI motility in transported horses, as has been reported previously, but decreased GI motility was not observed after confinement. Decreased GI motility is consistent with well‐characterized sympathoadrenal neuroendocrine responses to transportation and GI problems, notably colic and colitis, are commonly associated with transportation of horses . Road transportation has been recently determined to influence fecal microbiome and metabolic responses to diet and exercise .…”
Section: Discussionmentioning
confidence: 60%
“…Abdominal auscultation also suggested decreased GI motility in transported horses, as has been reported previously, but decreased GI motility was not observed after confinement. Decreased GI motility is consistent with well‐characterized sympathoadrenal neuroendocrine responses to transportation and GI problems, notably colic and colitis, are commonly associated with transportation of horses . Road transportation has been recently determined to influence fecal microbiome and metabolic responses to diet and exercise .…”
Section: Discussionmentioning
confidence: 60%
“…Replication of the non-commercial transport experience in an experimental situation is challenging and would not reflect the variety of road conditions experienced in reality [5]. Consequently, a retrospective survey-based approach has been used in previous studies to evaluate the risk of injury during equine transport [6,7,27,29,30]. To date, surveys aimed at evaluating these risk factors in the non-commercial transport of equines have been conducted in Australia [6,27,30], New Zealand [7] and the United States [29].…”
Section: Introductionmentioning
confidence: 99%
“…Transportation has been identified as a stressor for horses, and has been associated with several adverse outcomes including injury, respiratory and gastrointestinal disease [1][2][3][4][5][6]. We have recently shown that 12 hours' transportation is associated with ulceration of the gastric squamous mucosa in fasted horses, associated with increased pH of gastric content, and possibly with decreased gastrointestinal motility in horses fed 1 h and 6 h prior to transportation [7].…”
Section: Introductionmentioning
confidence: 99%